Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Rezension zu L.J. Issing & P. Klimsa (Hrsg.) (2009). Online-Lernen. Handbuch für Wissenschaft und Praxis. München: Oldenbourg Verlag - Eickelmann, Birgit (Journal for Educational Research Online)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Selbstoptimierende Systeme des Maschinenbaus - Definitionen, Anwendungen, Konzepte - Adelt, P.; Donoth, J.; Gausemeier, Jürgen; Henkeler, S.; Kahl, S.; Klöpper, B.; Krupp, A.; Münch, E.; Oberthür, S.; Paiz, C.; Porrmann, M.; Radkowski, R.; et al.

Verlässlichkeit selbstoptimierender Systeme - Potenziale nutzen und Risiken vermeiden - Dell'Aere, A.; Hirsch, M.; Klöpper, B.; Koester, M.; Krüger, M.; Krupp, A.; Müller, T.; Oberthür, S.; Pook, S.; Priesterjahn, C.; Romaus, C.; Schmidt, A.; et al.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Musterbasiertes Re-Engineering von Softwaresystemen - Meyer, Matthias

Dienste-Infrastrukturen für eLearning – Konzeption, Aufbau und Betrieb - Brennecke, Andreas; Finke, Stefan; Oevel, Gudrun; Roth, A. (Hochschulentwicklung innovativ gestalten – Das Projekt Locomotion an der Universität Paderborn)